A História da Comunidade Quilombola de Olaria, em Irará - Bahia e a Luta pela Terra na Contemporaneidade - dos Santos, Jucélia Bispo (Universidade Federal Rural do Rio de Janeiro, 2015)
This article emphasizes the tracks social subject in community preserves of pottery, Irará-Bahia. Stands out as source quilombos occurred in the Organization of regional space, which was formed by the Devil's colonization project Liu. The origin of this community is associated with this process of resistance, which took place especially in the late 19th century, when the sugar economy entered into crisis and the slave intinerâncias entries in the region searched has increased. Hence now there is a constant movement of a population of black percorria microregion (including in this example Irará) in search of land to work. Also presents the current daily marginated, which is the need to acquire material goods necessary for the construction of human dignity, since the history of these subject is marked by a collective trajectory of suffering and poverty. Were also described their traditions and cultural practices.